Approaches to Hungarian: Vol. 16 Papers from the 2017 Budapest Conference - Irene Vogel (Approaches to Hungarian, 2020)
This volume contains selected papers from the 13th International Conference on the Structure of Hungarian (Budapest, 2017).The contributions address current issues in Hungarian linguistics, including comparisons with other languages (e.g., English, German, Turkish, Arabic, Spanish). Specifically, the phonetics and phonology papers present experimental and corpus studies of /h/ voicing, the acoustics of Hungarian word stress, and vowel harmony in harmonically mixed stems. The papers on syntax and semantics discuss object agreement and its locality restrictions, equative markers in German and Hungarian diachronically and synchronically, anaphoric possessor strategies and definite article distribution, and the semantics of various aspectual adverbs. Experimental studies of information structure examine the linear placement of textually given topical constituents post-verbally, exhaustivity inferences with focus partitioning in German, English and Hungarian, and contextual factors licensing Hungarian structural focus. The broad range of topics ensures that this volume will interest scholars of Hungarian and theoretical linguists more generally.